QUANTITATIVE STUDIES ON THE MIXED LYMPHOCYTE INTERACTION IN RATS : I. CONDITIONS AND PARAMETERS OF RESPONSE - Wilson, Darcy B. (The Rockefeller University Press, 1967)
Some of the conditions and parameters of the proliferative response in the mixed lymphocyte interaction have been studied with the use of culture inocula consisting of lymphoid cells from various immunogenetically diverse, isogenic strains of rats. Procedures are described by which consistent culture responses can be obtained which are measurable in terms of incorporation of radioactive thymidine into a trichloroacetic acid precipitable cell fraction. Results of experiments with this "mixed lymphocyte interaction" show that (a) Incorporation of thymidine into the mixed cultures is detectable only during and after the 4th day of incubation. Use of culture inocula derived from the thoracic duct or partially purified suspensions of lymphocytes from the peripheral blood provides further evidence that it is the small lymphocyte which synthesizes DNA in these cultures. The addition of peritoneal exudate cells, presumably containing some macrophages, to the mixed lymphocyte cultures does not alter the kinetics of the response. (b) Proliferative responses occur in mixed cultures of cells only when the donors differ by alleles at the important Ag-B histocompatibility locus. (c) Proliferative reactivity in mixed cultures of lymphocytes from parental and hybrid donors is unidirectional. With the use of chromosomally marked cells from donors of different sexes, it was established that only parental lymphocytes are dividing in mixed cultures of parental and hybrid cells. The results of these experiments strongly support the premise that the proliferative response in mixed cultures of lymphocytes represents a de novo immunologic reaction on the cellular level against histocompatibility antigens.